2013
DOI: 10.1038/leu.2013.6
|View full text |Cite
|
Sign up to set email alerts
|

Notch-directed microenvironment reprogramming in myeloma: a single path to multiple outcomes

Abstract: Multiple myeloma is a deadly hematopoietic malignancy. Despite therapeutic advances such as autologous stem cell transplantation and novel chemotherapeutics, multiple myeloma remains incurable. Multiple myeloma cell localization in the bone marrow and the cross-talk with the bone niche trigger dramatic alterations in the bone marrow microenvironment critical for tumor progression, resistance to therapies and osteolytic bone destruction. It does not surprise that the molecular bases of such fatal interaction ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 118 publications
2
80
0
Order By: Relevance
“…The underlying basis appears complex, as, for instance, activation of Notch signaling can have either oncogenic or tumor-suppressive effects in tumors of the same type. As is the case in stem cell differentiation, this apparent complexity is likely to be the result of crosstalk between Notch signaling and other signaling pathways (Hurlbut et al, 2007;Koch and Radtke, 2010;Louvi and Artavanis-Tsakonas, 2012;Colombo et al, 2013).…”
Section: Proliferation and Apoptosismentioning
confidence: 99%
“…The underlying basis appears complex, as, for instance, activation of Notch signaling can have either oncogenic or tumor-suppressive effects in tumors of the same type. As is the case in stem cell differentiation, this apparent complexity is likely to be the result of crosstalk between Notch signaling and other signaling pathways (Hurlbut et al, 2007;Koch and Radtke, 2010;Louvi and Artavanis-Tsakonas, 2012;Colombo et al, 2013).…”
Section: Proliferation and Apoptosismentioning
confidence: 99%
“…Recently, it has been demonstrated that NOTCH2 is highly expressed in MM cells and that it is a key regulator of MM pathogenesis (Colombo et al 2013). In particular, it has been reported that the activation of the NOTCH2, which interacts with Wnt components, induces an exacerbated growth of MM cells and accelerated the course of the disease by promoting cancer stem cell self-renewal (Xu et al 2012a) and resistance to chemotherapeutic agents (Xu et al 2012b).…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…Aberrations in Notch signaling have also been linked to several hematological malignancies, including T-cell acute lymphoblastic leukemia (T-ALL), acute myeloid leukemia (AML), lymphoma and multiple myeloma (MM) [6,12]. The role of Notch signaling in hematopoiesis and in hematopoietic SC (HSC) development and maintenance has been extensively reviewed by Bigas and Espinosa [30], the fundamental finding being that activation of the Notch pathway is necessary for HSCs maintenance, and its inhibition results in HSCs differentiation and depletion [31].…”
Section: Notch and Ticsmentioning
confidence: 99%
“…The Notch family of proteins includes a total of four highly homologous receptors (Notch-1, Notch-2, Notch-3, Notch-4) with important roles in the regulation of various processes, including neurogenesis, gliogenesis, myogenesis, vasculogenesis, hematopoiesis and epidermal development [6]. The Notch system is involved in the homeostasis of adult tissues by promoting self-renewal of SCs, determining cell fate (such as commitment towards T or B cell lineage) and regulating the differentiation of many cell types.…”
Section: The Notch Pathwaymentioning
confidence: 99%